Addition of metallic reinforcement enhanced deformation and properties of ceramic reinforced composite by adapting ECAP with increment number of passes. (1st May 2019) - Sureshkumar, P; Uvaraja, V C; Rajakarunakaran, S
Abstract: This paper investigates the Microstructure, Mechanical, Corrosion and Tribological properties of metallic (Cu(NO2 )3 )p and ceramic( β -Si3 N4 )p reinforced Hybrid Aluminum Metal Matrix Composite processed by Equal Channel Angular Pressing (ECAP) at room temperature. The porosity of cast composite is reduced by increasing the number of ECAP passes. Scanning Electron Microscope (SEM), x-ray diffraction (XRD) and Energy Dispersive Spectroscopy (EDAX) are utilized to investigate the severely deformed microstructure, crystal structure and elemental analysis of composite. Corrosion test is carried out by salt spray test. Tribological properties such as wear and coefficient of friction are analyzed using Pin-on-Disc machine. The test results indicate that the mechanical properties of composite with fixed weight proportion of ceramic reinforcement along higher metallic reinforced sample with ECAP passes show higher value, particularly in terms of hardness and compressive strength as against the annealed composite and cast composite where the value increases with the increment number of passes. Similarly, tribological properties also increase with higher reinforcement content and more number of passes of ECAP process. But in the case of corrosion test, the results are opposite. The corrosion resistance of sample decreases with more number of passes of ECAP process as compared to cast composites because the material attains fine grain as the number of passes increase.